Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.expthermflusci.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the heater size effect on subcooled pool boiling heat transfer of FC-72 in microgravity

Abstract: Experiments of highly subcooled nucleate pool boiling of FC-72 with dissolved air were conducted on a large scale silicon chip (2 Â 2 Â 0.05 cm 3 , denoted as chip S 2 Â 2) in short-term microgravity condition and normal gravity condition by utilizing the drop tower in Beijing respectively. The results were compared with published results of a smaller scale chip (1 Â 1 Â 0.05 cm 3 , denoted as chip S 1 Â 1) both in normal gravity condition and microgravity condition, to study the heater size effect on boiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The results were consistent with those of Park and Bergles [116]. Wang et al [117] reported a different trend by conducting experiments in subcooled FC-72 on the silicon chips with the areas of 20×20 mm 2 and 10×10 mm 2 . The NBHT coefficient of the smaller heater was significantly higher than that of the larger one, regardless of the heat flux.…”
Section: Effects Of Surface Size Surface Orientation and Surface Agingsupporting
confidence: 88%
See 1 more Smart Citation
“…The results were consistent with those of Park and Bergles [116]. Wang et al [117] reported a different trend by conducting experiments in subcooled FC-72 on the silicon chips with the areas of 20×20 mm 2 and 10×10 mm 2 . The NBHT coefficient of the smaller heater was significantly higher than that of the larger one, regardless of the heat flux.…”
Section: Effects Of Surface Size Surface Orientation and Surface Agingsupporting
confidence: 88%
“…Lu et al [119] and Mori et al [120] also found similar result on the silicon wafer and porous copper surface, respectively. It is worth mentioned that CHF was found to increase with the heater size under microgravity in the studies of Wang et al [117]. The reason of the opposite trends might be a result of the different heat transfer mechanism of various heater sizes under the microgravity condition.…”
Section: Effects Of Surface Size Surface Orientation and Surface Agingmentioning
confidence: 92%